SCIENTIFIC AND THEORETICAL FUNDAMENTALS FORMATION OF CREATIVE THINKING DESIGNERS (Pedagogy of Higher and Secondary Education, 2022)
In this article is studied question about creative abilities in common and creating creative views in the way of parts.
Keywords: creative abilities; designers views; productive views